Differences in serum and plasma levels of microRNAs and their time-course changes after blood collection - Wakabayashi, Ichiro; Marumo, Mikio; Ekawa, Kazumi; Daimon, Takashi (Practical laboratory medicine, 2024)
Serum and plasma are used for measurements of microRNAs (miRNAs) as biomarkers of various diseases. However, no consistent findings have been obtained regarding differences in serum and plasma levels of miRNAs. The purpose of this study was to clarify differences in serum and plasma levels of total miRNAs and their time-course changes after blood collection. Venous blood was collected from healthy men, and samples were prepared at the time points of 0, 15, 30, 60 and 180 min after blood collection for plasma and after clot formation for serum. Levels of total miRNAs were analyzed by the hybridization method using the 3D-Gene miRNA Oligo chip. About one third of 2632 miRNAs tested showed levels high enough for comparison of serum and plasma levels and for investigation of their time-course changes. Levels of 299 miRNAs at time 0 were significantly different in serum and plasma. Levels of representative platelet-derived miRNAs including miR-185-5p, -22-3p and -320b were significantly higher in plasma than in serum, while levels of representative erythrocyte-derived miRNAs including miR-451a, -486-5p and -92a-3p were not significantly different in serum and plasma. Plasma levels of 173 miRNAs and 6 miRNAs showed significant decreasing and increasing tendencies, respectively, while there were no miRNAs in serum that showed significant time-course changes. The results suggest that careful attention should be paid when comparing serum and plasma levels of miRNAs and that plasma samples should be prepared early after blood collection. •Levels of 299 miRNAs were significantly different in serum and plasma.•Levels of several platelet-derived miRNAs were higher in plasma than in serum.•Several erythrocyte-derived miRNA levels were not different in serum and plasma.•Plasma levels of 173 miRNAs tended to decrease with time after blood collection.•There were no miRNAs in serum that showed significant time-course changes.